Inducing high nitrite accumulation via modulating nitrate reduction power and carbon flux with Thauera spp. selection. (June 2022) - Fan, Jiarui; Du, Rui; Li, Cong; Liu, Qingtao; Peng, Yongzhen
Graphical abstract: Highlights: Rapid NO2 − accumulation over 80% can be induced by improving NO3 − reduction power. Carbon flux was more shared in PD than assimilation and EPS production at high NLR. Thauera was highly enriched as core bacteria above 70% despite different inoculum. Sludge retention time had little impact on carbon metabolism and nitrate reduction. Abstract: Partial-denitrification (PD, NO3 − -N → NO2 − -N) is emerging as a promising approach for application of anaerobic ammonium oxidation (anammox) process. In this study, stable PD with high nitrite (NO2 − -N) accumulation was achieved by modulating nitrate (NO3 − -N) reduction activity and carbon metabolism. With the influent NO3 − -N increasing from 30 to 200 mg/L, specific NO3 − -N reduction rates ( rno3 ) were significantly improved, corresponding to the nitrate-to-nitrite transforming ratio (NTR) increasing rapidly to 80.0% within just 70 days. The required COD/NO3 − -N decreased from 4.5 to 2.0 and the carbon flux was more shared in NO3 − -N reduction to NO2 − -N. Notably, Thauera spp. as core denitrifying bacteria was highly enriched with the relative abundance of 70.5%∼82.1% despite different inoculations. This study provided a new insight into inducing high NO2 − -N accumulation and promoting practical application of anammox technology.